Workload Indicators of Staffing Need (WISN) for the Required Estimation of Nursing Staff in a Hemodialysis Unit - Winvi, Feli Clarisa; Nasution, Sri Lestari Ramadhani; Ginting, Chrismis Novalinda (Folia Medica Indonesiana, 2023)
Highlights: This article presents an understudied topic of nursing workloads in a hemodialysis unit and concludes that directly and indirectly productive activities occupied the majority of the nurses' working time. An analysis using the Workload Indicators of Staffing Need produced a general report that may prompt re-evaluation of nursing staff requirements and policy-making for workload distribution. Abstract The number of hemodialysis patients continues to increase almost every month, while the number of nurses in the Hemodialysis Unit at Rasyida Renal Specialist Hospital, Medan, Indonesia, remains constant. This situation has increased the nurses' workload and responsibilities. Therefore, it is necessary to examine the balance between the workload and the number of required nursing staff in the Hemodialysis Unit at Rasyida Renal Specialist Hospital. This study aimed to identify the optimal number of nursing staff required in the Hemodialysis Unit at the hospital in 2022. This study used a mixed-methods approach using the Workload Indicators of Staffing Need (WISN) method. This study included 44 nurses working in the Hemodialysis Unit at Rasyida Renal Specialist Hospital. Primary data included questionnaires, observations, and interviews during working hours, while secondary data included document reviews and staffing data. WISN calculations showed that the Hemodialysis Unit required a total of 65 nursing staff. In other words, an addition of 21 nursing staff was needed to meet the current workload. In conclusion, the current human resources available are not sufficient, and the workload is beyond the capacity of the nursing staff at the hospital.